Polyphenols: Nature’s Gift as dietary phytoconstituents against different human ailments - Thapa, Rojina; Thapa, Rambika; Mahat, Sunita; Thapa, Rupak (Nepal Journal of Biotechnology, 2019)
Recently, researches and scientists are showing a lot of interests in bioactive compounds of plants and its products as these constituents are of high valued. Polyphenols are phytochemical constituents which are the integral components in plants and their products that are associated with defensive mechanism against infections and various oxidative stress by free radicals. Green tea, fruits, vegetables, cereals and red wines are rich sources of polyphenolic constituents which attributes prevention from infections and diseases because of its antioxidant properties, anti-diabetic properties, and radical scavenging properties. Oxidative stress which is the primary reason for different ailments in humans is due to the free radicals that are present even during the normal health condition. Polyphenolic acids like cinnamic acid, romarinic acid, stilbenes like resveratrol, flavonoids like catechin, taxifolin, quercetin, and lignans like sesamin, pinoresinol, podophyllotoxin etc. are found to be effective against wide range of human diseases like oxidative stress, cardiovascular disorder, neurodegenerative diseases, aging, and cancer. These phytoconstituents prevent the diseases and provide relieving sensation via different mechanisms. Here, the study shows the importance of polyphenols with respect to the relevance of human health. As there are the promising applications of various bioactive constituents in a wide range of disease, further research should be encouraged on the mechanism of action and bioavailability of polyphenols.